Uso sistêmico do etoricoxib como adjunto ao tratamento periodontal não cirúrgico em pacientes portadores de periodontite agressiva : avaliação a curto prazo - Azoubel, Maria Cecilia Fonsêca (2008)
Aggressive periodontitis is an inflammatory type of periodontal disease which, although rare, generally affects individuals at an early age and is characterized by the rapid and debilitating destruction of the support periodontium. The pathogenesis of this pathology is related to primary etiologic factor, dental biofilm, associated to the immunoinflammatory response of susceptible host to this aggression. The purpose of this study was to assess the effect of short duration treatment with etoricoxib as adjuvant therapy to scaling and root planing (SRP) on prostaglandin E2 (PGE2) levels and the clinical and radiographic parameters in aggressive periodontitis. Patients were randomly allocated to TEST or CONTROL (N=10 in each group) and submitted to SRP and treatment with 120 mg/day of etoricoxib or placebo during 7 days. Probing depth (PD), clinical attachment level (CAL), gingival recession (GR), visible plaque index (VPI), bleeding on probing (BOP), measurement of the linear distance (LD) and analysis of the gray levels (GL) were recorded before and one month after the therapies. The visual analysis from video and negatoscope and digital subtraction radiographic was made in beginning and in the final experimental period (30 days). The PGE2 dosage in the gingival crevicular fluid (GCF) was measured by radioimmunoassay at the beginning, and 7 and 30 days afterwards. No significant difference was observed between the groups in the clinical parameters at the end of the experimental period, although both groups presented significant improvement in all the variables examined. There was a decrease in CAL from 5.54±0.47 mm to 3.59±0.53 mm in the TEST group and from 5.92±1.10 to 3.69±0.80 mm in the CONTROL group. A significant reduction in PGE2 was found after 7 days of treatment. The LD measurement was shown to differ between the groups. In conclusion, etoricoxib did not promote additional improvement in the clinical parameters, however it produced an initial reduction in the PGE2 levels in the GCF, which could be related to the discrete improvement in the bone condition.